IMPLEMENTASI PENDEKATAN SCIENTIFIC MODEL PROJEC BASED LEARNING DENGAN MEDIA AUDIO-VISUAL UNTUK MENINGKATKAN KREATIVITAS DAN MOTIVASI BERWIRAUSAHA DI SMK NEGERI 2 JIWAN KABUPATEN MADIUN - Trirahmatia, Bintari; Joyoatmojo, Soetarno; Santosa, Djoko (Jurnal Pendidikan Insan Mandiri, 2016)
The objective of this research is to investigate the improvement of learning creativity and entrepreneurial motivation through the implementation of the scientific approach of Project Based Learning model with audio-visual media on the Craft and Entrepreneurship subject matter of the Students in Grade X Accounting 3 of State Vocational High School 2 of Jiwan, Madiun Regency.This research used the classroom action research with the descriptive qualitative and quantitative method (mixed method). Its objects were the students as many as 36 in Grade XI Accounting 3 of the aforementioned school. The data of research were collected through observation, in-depth interview, field note, questionnaire, and documentation.The result of research shows that the implementation of the scientific approach of PjBL model with audio-visual media creates an effective and exciting learning, improves the students? critical thinking skill to solve problems and motivates them to create creative ideas in learning and craftsmanship so that in the long-term, it improves their entrepreneurial motivation. Based on the questionnaire, the students? learning creativities also improve following the implementation of the scientific approach of PjBL model with audio-visual media. Prior to the treatment, their average percentage is 73%, and following the treatment, it becomes 89%. In addition, their entrepreneurial motivation also improves. Prior to the treatment, the average percentage is 73%, and following the treatment it becomes 87%. The statistical calculation of the significance value (2-tailed) shows that the value of t-test is 0.000. It is less than 0.050 meaning that H0 is rejected. Thus, there is a significant difference of average score of leaning creativity and entrepreneurial motivation prior to the treatment (pre-test) and following the treatment (post-test). Keywords: Scientific approach, Project Based Learning, Audio-Visual, Learning Creativity, Entrepreneurial Motivation